Selective extraction of silver from semiconductor waste - Mat, Hanapi; Tang, B. S.; Y., Yuliusman; Othman, Norashikin (1999)
Semiconductor waste can cause a serious problem in term of storage and pollution since it high concentration of heavy metals. One possible alternative to treat this waste is to recover the metals especially precious metals such as silver. In this work, an attempt was made to recover the silver from semiconductor waste obtained from local semiconductor company using leaching and liquid-liquid extraction processes. Characteristics of the waste was investigated initially and found that it contains 21.57%of water and 14.73% of organic matter with the density of 2.87gcm-3. 7.55% (w/w) of silver was found in the waste and existed mostly in the form of Ag and AGC1. In the leaching experiment, it was found that HC1 gives better silver leaching. The extent of silver leaching increases with increasing the chloride concentration which can be achieved by either increasing the HC1 concentration or addition of high NaC1 concentration. In the extraction studies, dithizone is capable to extract silver selectively at wide range of pH. It was also found that at pH higher than 6, copper and iron precipitation were occurred.